An Overview of Recent Insights into the Response of TLR to SARS-CoV-2 Infection and the Potential of TLR Agonists as SARS-CoV-2 Vaccine Adjuvants - Mohammad Enamul Hoque Kayesh; Michinori Kohara; Kyoko Tsukiyama-Kohara (Viruses, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to coronavirus disease (COVID-19), a global health pandemic causing millions of deaths worldwide. However, the immunopathogenesis of COVID-19, particularly the interaction between SARS-CoV-2 and host innate immunity, remains unclear. The innate immune system acts as the first line of host defense, which is critical for the initial detection of invading pathogens and the activation and shaping of adaptive immunity. Toll-like receptors (TLRs) are key sensors of innate immunity that recognize pathogen-associated molecular patterns and activate downstream signaling for pro-inflammatory cytokine and chemokine production. However, TLRs may also act as a double-edged sword, and dysregulated TLR responses may enhance immune-mediated pathology, instead of providing protection. Therefore, a proper understanding of the interaction between TLRs and SARS-CoV-2 is of great importance for devising therapeutic and preventive strategies. The use of TLR agonists as vaccine adjuvants for human disease is a promising approach that could be applied in the investigation of COVID-19 vaccines. In this review, we discuss the recent progress in our understanding of host innate immune responses in SARS-CoV-2 infection, with particular focus on TLR response. In addition, we discuss the use of TLR agonists as vaccine adjuvants in enhancing the efficacy of COVID-19 vaccine.